Simultaneous experimental evaluation of pulse shape and deadtime phenomenon of GM detector - AKYÜREK, TAYFUN (NATURE RESEARCH, 2021)
Analysis of several pulse shape properties generated by a Geiger Mueller (GM) detector and its dependence on applied voltage was performed. The two-source method was utilized to measure deadtime while simultaneously capturing pulse shape parameters on an oscilloscope. A wide range of operating voltages (600-1200 V) beyond the recommended operating voltage of 900 V was investigated using three radioactive sources (Tl-204, Cs-137, Na-22). This study investigates the relationship between operating voltage, pulse shape properties, and deadtime of the detector. Based on the data, it is found that deadtime decreases with increasing voltage from 600 to 650 V. At these low voltages (600-650 V), the collection time was long, allowing sufficient time for some recombination to take place. Increasing the voltage in this range decreased the collection time, and hence deadtime decreased. It is also observed that rise and fall time were at their highest at these applied voltages. Increasing the voltage further would result in gas multiplication, where deadtime and pulse width are observed to be increasing. After reaching the maximum point of deadtime (similar to 250 mu s at similar to 700 V), deadtime started to exponentially decrease until a plateau was reached. In this region, it is observed that detector deadtime and operating voltage show a strong correlation with positive pulse width, rise and fall time, cycle mean, and area. Therefore, this study confirms a correlation between detector deadtime, operating voltage, and pulse shape properties. The results will validate our hypothesis that deadtime phenomena at different operating voltages are phenomenologically different.